Decrease in Statewide Antipsychotic Prescribing after Implementation of Child and Adolescent Psychiatry Consultation Services - Barclay, Rebecca P. (Health Serv Res, 2017)
OBJECTIVE: To learn if a quality of care Medicaid child psychiatric consultation service implemented in three different steps was linked to changes in statewide child antipsychotic utilization. DATA SOURCES/STUDY SETTING: Washington State child psychiatry consultation program primary data and Medicaid pharmacy division antipsychotic utilization secondary data from July 1, 2006, through December 31, 2013. STUDY DESIGN: Observational study in which consult program data were analyzed with a time series analysis of statewide antipsychotic utilization. DATA COLLECTION/EXTRACTION METHODS: All consultation program database information involving antipsychotics was compared to Medicaid pharmacy division database information involving antipsychotic utilization. PRINCIPAL FINDINGS: Washington State's total child Medicaid antipsychotic utilization fell from 0.51 to 0.25 percent. The monthly prevalence of use fell by a mean of 0.022 per thousand per month following the initiation of elective consults (p = .004), by 0.065 following the initiation of age/dose triggered mandatory reviews (p < .001), then by another 0.022 following the initiation of two or more concurrent antipsychotic mandatory reviews (p = .001). High‐dose antipsychotic use fell by 57.8 percent in children 6‐ to 12‐year old and fell by 52.1 percent in teens. CONCLUSIONS: Statewide antipsychotic prescribing for Medicaid clients fell significantly at different rates following each implementation step of a multilevel consultation and best‐practice education service.